Peningkatan Kemampuan Berpikir Kreatif Matematika Melalui Model RME (Realistic Mathematics Education) di Kelas IV Sekolah Dasar - Rifal Firmansyah; Sungging Handoko; Iwan Gunawan (EDUCARE, 2019)
This study is entitled '’Increasing Mathematical Creative Thinking Ability through the RME (Realistic Mathematics Education) Model in Class IV of Primary Schools”. This research aims to determine the application of the RME (Realistic Mathematics Education) model to improve the ability of mathematical creative thinking of fourth grade students and to find out the improvement of class IV mathematical creative thinking skills through the RME (Realistic Mathematics Education) Model. The theory used in this research is Shoimin is theory (2017). The method used in this study is a quasi-experimental method with a quantitative approach. Participants in this study consisted of 2 classes namely the experimental class and the control class. In this study, data were collected using observation and test techniques. In this study us the RME (Realistic Mathematics Education) model, which shows that there is an increase in mathematical creative thinking skills in fourth grade students of Muhammadiyah 6 Elementary School, Bandung City. This can be seen from the results of the pretest and posttest calculations in the experimental class.